2013
DOI: 10.1177/0363546513507426
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Chondrocyte and Synovial Cell Death After Exposure to Commonly Used Anesthetics

Abstract: Apoptosis inhibition may be an effective strategy in minimizing chondrocyte and synovial cell death after exposure to anesthetics. Further investigation is clinically warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 58 publications
0
38
0
Order By: Relevance
“…These effects were demonstrated by the increased chromatin condensation and nuclear fragmentation with enhanced cleavage of caspase-3, the appearance of a sub-G 0 /G 1 peak in the flow cytometry assay, and the increased percentage of apoptotic cells in the annexin V binding assay. The induction of apoptosis by LAs in chondrocytes has been reported by several studies using in vitro cellular models [1,11] . Recently, Grishko et al have suggested that a mitochondrial pathway is involved in LA-induced apoptosis, which is associated with mitochondrial dysfunction resulting from damage to the mitochondrial genome [11] .…”
Section: Wwwchinapharcom Lee Yj Et Almentioning
confidence: 78%
See 1 more Smart Citation
“…These effects were demonstrated by the increased chromatin condensation and nuclear fragmentation with enhanced cleavage of caspase-3, the appearance of a sub-G 0 /G 1 peak in the flow cytometry assay, and the increased percentage of apoptotic cells in the annexin V binding assay. The induction of apoptosis by LAs in chondrocytes has been reported by several studies using in vitro cellular models [1,11] . Recently, Grishko et al have suggested that a mitochondrial pathway is involved in LA-induced apoptosis, which is associated with mitochondrial dysfunction resulting from damage to the mitochondrial genome [11] .…”
Section: Wwwchinapharcom Lee Yj Et Almentioning
confidence: 78%
“…However, there are a number of reports concerning the toxic effects of LAs on cartilage and muscle [1,2] , in addition to the overt cartilage damage observed at the time of surgery. There is evidence supporting a chondrotoxic effect of LAs on articular chondrocytes from several recent studies that have demonstrated detrimental effects of LAs on chondrocyte viability and cartilage histology [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous meta-analyses have demonstrated that the single-dose IA morphine34, bupivacaine567, ropivacaine8, clonidine9 or the combination of morphine and bupivacaine1011 were effective in pain relief. However, it is commonly known that IA local anesthetics must be used cautiously due to the concern of chondrotoxicity12, especially for bupivacaine13141516171819, levobupivacaine131419, ropivacaine13141617, mepivacaine17 and lidocaine13161820.…”
mentioning
confidence: 99%
“…Grishko et al reported that caspase‐3 and caspase‐9 increase in human chondrocytes following LA exposure, which induced apoptosis of chondrocytes. Rao et al demonstrated that the LA increase the activity of caspase‐3 in chondrocytes, and the LA‐induced chondrocyte death was significantly reduced after treatment of pan‐caspase inhibitor (z‐vad‐fmk). That study reported that caspases play a potential role in LA induced chondrocyte death.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have investigated the possibility of avoiding LA‐induced chondrocyte death by using opioid injections instead of LA injections . One study suggested that apoptosis inhibition may be an effective strategy for minimizing chondrocyte death after exposure to LA . However, no study has suggested any other method of protecting chondrocytes from the adverse effects of LA.…”
mentioning
confidence: 99%